2011
DOI: 10.1002/cphc.201100098
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Stable Silver Subsurface Ion‐Exchanged Glasses for SERS Applications

Abstract: We report on the formation of silver subsurface ion-exchanged metal oxide (silver SIMO) glasses and their surface-enhanced Raman scattering (SERS) activity. The samples were prepared by a combined thermal and chemical three-step methodology and characterized by transmission electron microscopy (TEM), atomic force microscopy (AFM), environmental electron scanning microscopy (ESEM), and UV/Vis spectroscopy. This unique method provides SERS substrates with protection against contamination and strong, reliable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…In our earlier studies, no Raman band was observed for the Ag ion exchanged glass samples annealed at the different temperatures which gave a clear indication that the silver NCs were embedded in the glass matrix as metallic silver clusters and not respond to Raman spectroscopy. Simo et al, reported the SERS studies of Ag ion exchange samples after removing the glass layer on the surface of the Ag NCs . Our results focused only on the surface concentration of Ag + against antimicrobial activities.…”
Section: Resultsmentioning
confidence: 94%
“…In our earlier studies, no Raman band was observed for the Ag ion exchanged glass samples annealed at the different temperatures which gave a clear indication that the silver NCs were embedded in the glass matrix as metallic silver clusters and not respond to Raman spectroscopy. Simo et al, reported the SERS studies of Ag ion exchange samples after removing the glass layer on the surface of the Ag NCs . Our results focused only on the surface concentration of Ag + against antimicrobial activities.…”
Section: Resultsmentioning
confidence: 94%
“…SERS substrates have been prepared by imbedding Ag or Au NPs in soda-lime glass [75,76,77]. A combined thermal and chemical methodology was developed to synthesize Ag NPs in soda-lime silicate glass [75].…”
Section: Resultsmentioning
confidence: 99%
“…A combined thermal and chemical methodology was developed to synthesize Ag NPs in soda-lime silicate glass [75]. Silver ions were introduced into glass by immersing glass slides in a 1:2 AgNO 3 /NaNO 3 molten salt bath mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Adenine is one such frequently studied biomolecule. Its intense surface‐enhanced Raman spectroscopy (SERS) signal has led to its frequent use as an example biomolecule to test and characterize SERS‐active substrates, for demonstration of single‐molecule detection, for detection of diseases and for determination of DNA hybridization, adsorption orientation, and quantification of nucleobase content . Furthermore, examining the spectral contribution of adenine and the other nucleobases has allowed for characterization of the adsorption of large complex biomolecules such as DNA and its components, as well as the cofactors flavin adenine dinucleotide (FAD) and nicotinamide adenine dinucleotide (NAD) .…”
Section: Introductionmentioning
confidence: 99%